Primary Black Hole Spin in OJ 287 as Determined by the General Relativity Centenary Flare - Valtonen, M. J.; Zola, S.; Ciprini, S.; Gopakumar, A.; Matsumoto, K.; Sadakane, K.; Kidger, M.; Gazeas, K.; Nilsson, K.; Berdyugin, A.; Piirola, V.; Jermak, H.; et al. (The Astrophysical Journal, 2016)
OJ 287 is a quasi-periodic quasar with roughly 12 year optical cycles. It displays prominent outbursts that are predictable in a binary black hole model. The model predicted a major optical outburst in 2015 December. We found that the outburst did occur within the expected time range, peaking on 2015 December 5 at magnitude 12.9 in the optical R-band. Based on Swift/XRT satellite measurements and optical polarization data, we find that it included a major thermal component. Its timing provides an accurate estimate for the spin of the primary black hole, χ =0.313+/- 0.01. The present outburst also confirms the established general relativistic properties of the system such as the loss of orbital energy to gravitational radiation at the 2% accuracy level, and it opens up the possibility of testing the black hole no-hair theorem with 10% accuracy during the present decade.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; black hole physics; quasars: general; quasars: individual: OJ 287; quasars: supermassive black holes